DEVELOPMENT OF PROPOSALS TO IMPROVE THE EFFICIENCY OF PUBLIC URBAN PASSENGER TRANSPORT - S. A. Azemsha (Вестник СибАДИ, 2019)
Introduction. Urban public transport plays an important role in modern cities. At the same time, the financial performance of public transport’s work is far from ideal. The purpose of the paper is to identify a promising area for increasing the payback of public urban passenger transport by application of different scientific methods.Materials and methods. The paper demonstrated the significant statistical relationship between the route’s payback of public urban passenger transport and the indicators of using the capacity of passenger vehicles. Moreover, the author presented the average value of the passenger stress coefficient. The author also proposed to increase the payback of public urban passenger transport based on the use of variable-length electric buses (modular vehicles), which allowed more precise adjustment to the capacity of passenger traffic.Results. Calculation examples showed that the use of modular passenger vehicles increased the public transport’s payback on 26%.Discussion and conclusions. As a result, the presence of the electric bus modules’ fleet of the same capacity allows the carrier flexibly adapting the existing passenger flow capacity. Therefore, such measures increase the passenger stress coefficient, reduce the spread of its values relative to the average value and lead to the increase in the payback of public passenger transport. The author recommends to substantiate the capacity of the module, to develop technology for carrying passengers by modular vehicles and to formulate technical requirements for the module design in further research.